Towards measuring the geographic and political resilience of the internet. (1st January 2013) - Baumann, Annika; Fabian, Benjamin
Given the importance of the internet for worldwide communication and services, its resilience against attacks, accidents, or attempts of misusing political control becomes critical for businesses and society. This article focuses on the question how vulnerable specific geographical regions are to an internet access disruption or to censorship-based impediments due to governmental control. In particular, a new metric is developed that measures the geographical internet resilience on a country level. For this purpose several indices based on geography, technologies as well as control are combined into a single, rank-based score indicating the internet resilience of a particular country compared to others.